2010
DOI: 10.1111/j.1523-5378.2010.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Helicobacter pylori Eradication on Time‐Trends in Brady/Hypokinesia and Rigidity in Idiopathic Parkinsonism

Abstract: Background:We examine the effect of eradicating Helicobacter in idiopathic parkinsonism (IP). Marked deterioration, where eradication-therapy failed, prompted an interim report in the first 20 probands to reach de-blinding. The null-hypothesis, “eradication has no effect on principal outcome, mean stride length at free-walking speed,” was rejected. We report on study completion in all 30 who had commenced post-treatment assessments.Methods:This is a randomized, placebo-controlled, parallel-group efficacy study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 51 publications
5
87
2
1
Order By: Relevance
“…A case study supports the candidature of overgrowth as a driver of rigidity [5] . Following H. pylori eradication, rigidity worsened in relation to onset of hydrogen breath test positivity, and improved on regaining negativity.…”
Section: Time Sequence In Response To Interventionmentioning
confidence: 94%
See 2 more Smart Citations
“…A case study supports the candidature of overgrowth as a driver of rigidity [5] . Following H. pylori eradication, rigidity worsened in relation to onset of hydrogen breath test positivity, and improved on regaining negativity.…”
Section: Time Sequence In Response To Interventionmentioning
confidence: 94%
“…Improvement in gait brady/hypokinesia following the successful blinded active treatment for H. pylori was mirrored by worsening of objectively measured upper limb flexor rigidity [5] . Rigidity worsened in year 1 with no further change over years 2 and 3.…”
Section: Time Sequence In Response To Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only two studies [19,23] attempted to correlate, in a cross-sectional manner, the presence of HP infection with worse PD severity. These studies were limited by small sample size [18e20, 22,23], open-label design [19,20,22], and/or the use of non-validated assessments of motor function [17,21,23]; several have been reported in abstract form only [20,22,23]. Thus, a recent Cochrane review concluded that further studies are required to address the gaps in knowledge regarding the role of HP infection in PD [24], and screening PD patients for HP status has yet to enter routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cycad is known to cause amyotrophic lateral sclerosis/parkinsonism-dementia complex among populations in Guam 4,5 and Japan's Kii Peninsula. 6 Studies have shown that H. pylori infection leads to poorer motor function, 7,8 and eradication leads to improvement in stride length. 7 Eradication of H. pylori also correlated with a reduction in inflammatory markers, 9,10 leading some authors to hypothesize that H. pylori infection leads to a chronic inflammatory process resulting in the destruction of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%